The use of whatsapp social media group for nutrition counselling among parents with children of congenital heart defects - Prabhu, Shruti; Prabhu, Atul; Sahu, Kavita Kiran (Penerbit Universiti Kebangsaan Malaysia, 2023)
Introduction; Ignorance about appropriate Infant and Young Child Feeding (IYCF) practices among parents with children of Congenital Heart Defects (CHD) can exacerbate malnutrition in these children leading to significant morbidity and mortality. The use of novel methods for Intensive Nutrition Counselling such as in a WhatsApp social media group can result in significant improvements in the child’s nutritional status. Objective of this study is to assess the efficacy of WhatsApp group for Intensive Nutritional Counselling to parents with children of CHD. Methods; This was a two-years prospective interventional study, one-group before-after study design, conducted at a tertiary care referral institute in Central India. Here, intervention is in the form of specialised focused nutrition counselling for parents of children with CHD through a WhatsApp social media group. Results; The majority of the patients 16 (30.0%) were between the ages of 7 and 12 months, and the most common diagnosis in 25 patients (48.9%) was a Ventricular Septal Defect (VSD). 68.0% of patient-families belonged to the lower socio-economic classes. Before the intervention, 71.1% of children (37 of 52) were found to be underweight, 35.5% of children were stunted and 65.6% of children were wasted. Post intervention, there was 50.0% improvement in weight and 14.0% improvement in height. This intervention particularly helped improve IYCF habits for the age group of 7-12 months. Post-intervention, all parents included the 8 food groups in their children’s diet, thus providing them with wholesome nutrition, whereas pre-intervention, parents only provided 2-3 food groups to children on a daily basis. Conclusions; This was the first study to explore the use of WhatsApp groups to educate parents of children with CHD about specific nutrition counselling, resulting in an improvement in all 3 child anthropometric indices.